2018
DOI: 10.1080/01480545.2018.1442474
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of cyclooxygenase-2, 12-lipoxygenase, inducible nitric oxide synthase-2 and surfactant protein D in lungs of patients with pulmonary injury caused by sulfur mustard

Abstract: Mustard lungs were associated with overexpression of COX-2 and 12-LO, which are responsible for inflammation, overproduction of free radicals and oxidative stress. Downregulation of iNOS2 and SF-D are probably the reason for lung disease and dysfunction among these patients. Therefore, the expression of these genes could be an important, routine part of the management of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Previous studies reported proinflammatory and inflammatory mediators in the bronchoalveolar lavage fluid, such as neutrophils, indicating injury to the bronchiole tree and a high incidence of bronchiole obliterans in SM-exposed survivors ( 11 , 16 ). Exposure to SM may induce chronic inflammation in the airways by the accumulation of inflammatory cells that release proinflammatory substances, such as cyclooxygenase-2 and 12-lipoxygenase, and reduce the production of protective substances, including surfactants ( 18 , 53 55 ). These pathological processes may successively deteriorate and result in small airway scarring that is undetectable by conventional imaging and spirometry tests in the early stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported proinflammatory and inflammatory mediators in the bronchoalveolar lavage fluid, such as neutrophils, indicating injury to the bronchiole tree and a high incidence of bronchiole obliterans in SM-exposed survivors ( 11 , 16 ). Exposure to SM may induce chronic inflammation in the airways by the accumulation of inflammatory cells that release proinflammatory substances, such as cyclooxygenase-2 and 12-lipoxygenase, and reduce the production of protective substances, including surfactants ( 18 , 53 55 ). These pathological processes may successively deteriorate and result in small airway scarring that is undetectable by conventional imaging and spirometry tests in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial to monitor individuals at high risk for any potential respiratory problems arising from SM exposure and employ alternative non-traditional monitoring methods to identify early-stage respiratory issues. While spirometry tests are the gold standard for measuring lung function, they have demonstrated a mixed picture of asthma, chronic obstructive pulmonary disease, and even normal results in SM-exposed survivors ( 18 21 ). Owing to the limited resources, conducting high-quality spirometry in many participants proved challenging; therefore, it was excluded from the study protocol in this article.…”
Section: Introductionmentioning
confidence: 99%
“…It eliminates chloride ions through intramolecular substitution to form cyclic sulfonium ions. These reactive intermediates alkylate DNA and other nuclear components inducing genotoxicity and cytotoxic damage that suppresses the immune system and inducible nitric oxide synthase (iNOS) signaling (Tahmasbpour, Ghanei et al 2019). Inhaled SM activates phagocytic leukocytes and inflammatory mediators that alter serum cytokines, C reactive protein (CRP), and soluble pro-apoptotic fasciclin 1 (Fas1) expression.…”
Section: Chemical Warfare Agentschlorine Phosgene and Sulfur Mustardmentioning
confidence: 99%
“…Therapies being explored include anti-inflammatories, antioxidants, and protease inhibitors, and some benefits from natural products are shown (Boskabady andFarhadi 2008, Hossein, Nasim et al 2008). Studies show restoration of surfactant may protect against SM-induced lung injury (van Helden, Kuijpers et al 2004), and that SP-D, a non-specific alveolar injury marker, may serve as an indicator of early respiratory disease (Starosta and Griese 2006, Sorensen 2018, Malaviya, Abramova et al 2020.…”
Section: Chemical Warfare Agentschlorine Phosgene and Sulfur Mustardmentioning
confidence: 99%
“…With respect to human disease, 12-LOXs and 12-HETE have been implicated in inflammatory lung disorders. Lungs of patients exposed to sulfur mustard toxin showed obstructive and restrictive lung disease and an increase in 12-LOX expression compared to control patients [ 129 ]. Furthermore, in tuberculosis, the expression of ALOX12 increases, and it is positively correlated with neutrophil count and bacterial load in the airway [ 130 ].…”
Section: 12-loxs In Pulmonary Inflammation and Diseasementioning
confidence: 99%